Sleep Disturbances, Bowel Movement Kinetics, and Travel Interruption With Bowel Preparation: A Bowel CLEANsing National Initiative Substudy. (21st September 2022) - Tse, Carmen; Barkun, Alan; Martel, Myriam; Nugent, Zoann; Epstein, Ian; Sey, Michael; Richard, Sultanian; von Renteln, Daniel; Singh, Harminder
Abstract : INTRODUCTION: We investigated sleep disturbances, bowel movement (BM) kinetics, and travel experience with different bowel preparation regimens in a substudy of patients enrolled in a randomized multicenter Canadian clinical trial. METHODS: Patients scheduled to have a colonoscopy between 7:30 am and 10:30 am (early morning) were randomized to (i) 4-L single-dose polyethylene glycol (PEG) given in the evening before, (ii) 2-L split-dose PEG (+bisacodyl 15 mg), or (iii) 4-L split-dose PEG. Patients scheduled to undergo a colonoscopy between 10:30 am and 4:30 pm (afternoon) were randomized to (iv) 2-L single-dose PEG (+bisacodyl 15 mg) in the morning, (v) 2-L split-dose PEG (+bisacodyl 15 mg), or (vi) 4-L split-dose PEG. Patients were asked to record information on BM kinetics, sleep, and travel to the endoscopy unit. Continuous and categorical variables were compared between groups using a Kruskal-Wallis test or χ 2 test, respectively. Intention-to-treat analyses were performed. RESULTS: Overall, 641 patients were included in this substudy. Patients undergoing early morning colonoscopies reported the most awakenings in the night when assigned to 4-L single-dose day-before PEG and the highest reduction in sleep hours when assigned to 4-L split-dose PEG. There were no significant between-group differences in urgent BMs, fecal incontinence episodes, or travel interruptions. Overall, 17% of those traveling for more than an hour had to stop for a BM during travel, with no significant difference between groups. DISCUSSION: Day-before and split-dose high-volume PEG regimens for colonoscopies scheduled before 10:30 am lead to the greatest sleep disturbance.